(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Involvement of the nervous system after viral infection is common. Certain viruses show neurotropism. Recent outbreak of severe acute respiratory syndrome CoV 2 (SARSCov- 2) virus has also exhibited neurotropic properties with various neurological manifestations. The pathophysiology of their neurotropism is not yet clearly known. The details of pathophysiology, clinical manifestation and management are expected to be explored in the near future. Here we review the Neurological manifestations of COVID-19 and the early experience in the National Institute of Neurosciences and Hospital. J Bangladesh Coll Phys Surg 2020; 38(0): 122-132